Loving life as it is : a Buddhist guide to ultimate happiness - Jigme Wangdrak, Chakung (Shambhala Publications, Inc., 2024)
"What makes you happy? What causes you to suffer? This book from an insightful new voice in Tibetan Buddhism offers practical wisdom and radical practices to embrace suffering--an inevitable part of human life--and find freedom, or happiness. Jigme Wangdrak is a contemporary teacher born and trained in eastern Tibet and based in California who is the unique holder of the Dudjom Lingpa lineage, reincarnation of renowned seventeenth-century treasure revealer Rigzin Longsel Nyingpo, and disciple of the great Tibetan female master Khandroma Kunzang Wangmo. In his first book, Jigme Wangdrak gives concrete advice on how to reorient your thinking--by embracing suffering, you can learn to see its roots, begin to work with it, and eventually let it go. This will allow you to fully savor happiness when it occurs. The first part of the book guides readers in recognizing and understanding suffering and happiness in their different forms. The second part of the book is dedicated to practice. Here, Jigme Wangdrak introduces the view and path of working directly with happiness and suffering. He conveys the steps, stages, and categories of mental exercises and practices that everyone--from beginner to VIP practitioner--can do to uproot the destructive effects of pain and sorrow that inevitably occur in life"--